Exploring Succession Planning within Small Family Owned Businesses - Mohamad, Norhidayah; Yahya, Salleh (2010)
Succession planning involves the training of next-generation family members to remain as the core value in a family business. However, small family firms are facing higher risks of failure because the succession process does not receive much interest. Therefore, it is vital to find effective ways to transfer the less tangible considerations to the next generation family members. This paper will addresses several issues of family business succession planning, with the purpose of identifying the main triggers for succession, criteria of a good successor and types of education required to run the family business. This research employs a multi-method approach, where the distribution of survey questionnaires, interviews and observations were conducted over time. A total of 388 family businesses answered the questionnaires and from the findings, tacit knowledge, achieved from informal education, was the contemporary way of transferring the business, from the owner to the successor. It also explains the current trend of succession planning and the key issues associated with successfully development principle successors. Moreover, this paper provides the relationship between succession issues and the performance of Malaysian small family businesses.